Analisis Kemandirian Belajar Mahasiswa Dalam Pembelajaran Berbasis Moodle Pada Flearn UKSW - Mila Chrismawati Paseleng; Dani Kusuma; Herry Sanoto (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
This research objective is to analyze students’ learning independence in the moodle-based learning at SWCU F-learn. This is a qualitative research by looking for the root of the research problem so that it can produce research findings. The subjects of this study were students from the Faculty of Teacher Training and Education which consisted of 20 students and then 3 subjects were selected with certain criteria. The research instrument used in this study were learning independence questionnaire, interview guidelines, and observation of the implementation of learning through Moodle. The validity and reliability of the instrument were reached by the validation from expert validators. The research was carried out by distributing questionnaires to students related to learning independence, then from students who had high, medium, and low learning independence, in-depth interviews and observations of the learning process were carried out through lectures. The data analysis used qualitative analysis by triangulating data sources, namely from questionnaires, interviews, and observations. The learning independence is the result of several integrated factors such as learning motivation, learning objectives, learning strategies, and self-evaluation. Subjects with low learning independence were caused by low learning motivation so that they did not have clear goals for the targets to be achieved. Subjects with moderate independence had good learning motivation but lack of follow-up and implications, so that less improvements were made. Meanwhile, subjects with high learning independence had high learning motivation and awareness, were able to design learning targets and make improvements simultaneously. In general, online-based learning using the Moodle/Flearn system requires good learning independence so that learning goals and achievements can run.